Keragaman dan Intensitas Infeksi Endoparasit Gastrointestinal pada Sapi Bali dengan Sistem Ekstensif di Kabupaten Kupang - I Gusti Komang Oka Wirawan; Melkianus Dedimus Same Randu; I Ketut Jaya (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Tanah Putih Village has the potential for the development of Bali cattle because it has extensive grazing land and the majority of farmers raise Bali cattle. The aim of the study was to obtain data on the diversity and intensity of gastrointestinal endoparasitic infection in Balinese cattle with an extensive breeding system in Tanah Putih Village, Kupang Timur District, Kupang Regency, East Nusa Tenggara Province. Gastrointestinal endoparasitic diversity was identify using sedimentation and flotation methods while the intensity of endoparasitic infection was carried out using McMaster method, while data on the diversity and rates of gastrointestinal endoparasitic infection were analyzed descriptively. The results of the study on the diversity of gastrointestinal endoparasites found there are five types of nematode worm eggs namely Haemonchus contortus, Oesophagostomum radiatum, Strongyloides papillosus, Bunostomum phlebotomum, and Trichostrongylus axei. Factors that support the diversity of endoparasites are feed sources, livestock populations, and grazing rotation. The average number of worm eggs found based on the total eggs per gram of faeces for Haemonchus contortus as many as 100 eggs and the other four types of worm eggs amounted to 50 eggs. The average number of eggs indicates that endoparasitic infections in these animals fall into the mild intensity category, is influenced by season, feed source, and age of livestock. The five types of gastrointestinal endoparasites found namely Haemonchus contortus, Oesophagostomum radiatum, Strongyloides papillosus, Bunostomum phlebotomum, and Trichostrongylus axei.